2013
DOI: 10.1111/mmi.12197
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of V‐nitrogenase genes in Anabaena variabilis by RNA processing and by dual repressors

Abstract: SummaryAnabaena variabilis ATCC 29413 fixes nitrogen in specialized cells called heterocysts using either a Mo-nitrogenase or a V-nitrogenase. V-nitrogenase structural genes, vnfDGK, as well as vnfEN form an operon with ava4025, located upstream of vnfDG that is repressed by fixed nitrogen and by Mo. The ava4025-vnfDGKEN operon is under the control of a Morepressible promoter located nearly 600 bp upstream of ava4025. Levels of vnfDG transcript were about 500-fold higher than ava4025, the first gene of the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…In contrast, we were able to verify primary transcription start sites upstream of nifB1 and hesA1 that matched the published sequence (7,39,46). Further, we demonstrated that the 5= ends of nifH1 and fdxH1 in the nif1 cluster, as well as the V-nitrogenase genes, vnfH and vnfDG, have processed RNA ends, not primary transcript ends (39,46,47). In a mutant strain that lacks xisA, the gene that makes the excisase that removes the 11-kb element from nifD1, the nifB1 promoter can no longer drive expression of the genes downstream from the excision element, resulting in little or no expression of those genes (46).…”
mentioning
confidence: 58%
“…In contrast, we were able to verify primary transcription start sites upstream of nifB1 and hesA1 that matched the published sequence (7,39,46). Further, we demonstrated that the 5= ends of nifH1 and fdxH1 in the nif1 cluster, as well as the V-nitrogenase genes, vnfH and vnfDG, have processed RNA ends, not primary transcript ends (39,46,47). In a mutant strain that lacks xisA, the gene that makes the excisase that removes the 11-kb element from nifD1, the nifB1 promoter can no longer drive expression of the genes downstream from the excision element, resulting in little or no expression of those genes (46).…”
mentioning
confidence: 58%
“…The xisA deletion strain, BP669, was created by introducing the mobilizable plasmid pBP669 into strain FD by conjugation. Single recombinants were selected by erythromycin resistance (Em r ), followed by isolation of double-recombinant mutants with the deleted copy of xisA, using sacB with sucrose selection (38) as described previously (39).…”
Section: Methodsmentioning
confidence: 99%
“…5). The assumption that V is acquired and the V-Nase genes are activated only when Mo becomes limiting for diazotrophic growth might be due to the oversimplified conditions used in laboratory experiments to study metal acquisition and homeostasis in A. vinelandii and other dinitrogen fixers (Bellenger et al, 2011;Pratte et al, 2013).…”
Section: Resultsmentioning
confidence: 99%